应用镭-226解读南极普里兹湾表层水的来源与运移 - 郑敏芳; 陈敏; 杨俊鸿; 张润; 马嫱; 杨伟锋; 邱雨生 (2010)
中国第22次南极科学考察航次(2005年12月至2006年1月)期间,利用Mn-纤维富集大体积表层海水中的rA同位素,并通过222rn直接射气法测量226rA的比活度,结果表明,普里兹湾表层水的226rA比活度变化为0.92--2.09 bQ/M3,平均值为1.61 bQ/M3,在深海区域表现出226rA含量高的特征。从空间分布看,表层水226rA比活度呈现出由湾内向湾外增加的反常态势,反映出不同rA含量水团的混合影响2。26rA比活度与盐度的关系证实研究海域表层水的rA含量主要受三种端元水体的混合所控制:其一为具有镭含量高、盐度高特征的南极夏季表层水;其二为低镭、低盐特征的冰融水;其三为高盐、中等镭含量的普里兹湾中深层水,该水体的226rA纯粹由海底沉积物间隙水向上扩散所维持。结合S-226rA示踪体系及上述三端元混合模型,计算出各组成水体的比例并描绘出它们的空间分布。南极夏季表层水的份额由湾外向湾内逐渐降低,并且在68°E断面向南影响范围较大;冰融水的比例由湾内向湾外降低,并且在湾内东部的高温水体中具有最大贡献;普里兹湾中深层水中受沉积物镭来源影响比较显著的区域出现在湾内西北部,其影响向湾外逐渐降低。冰融水与普里兹湾中深层水份额分别于普里兹湾湾顶东、西部出现高值的分布特征证实埃默里冰架前沿海流东进、西出的运移规律。 Surface waters were collected from the Prydz Bay of Antarctica for measurements of 226Ra activities during the 22nd China's antarctic research expedition(from December 2005 to January 2006).226Ra in large volume waters was extracted by Mn-fibers and measured by a 222Rn emanation method.Results show that 226Ra activity in the Prydz Bay ranges from 0.92 to 2.09 Bq/m3 with an average of 1.61 Bq/m3.High contents of 226Ra were observed at deep open-ocean stations,which induced an offshore increase of 226Ra activity.This unique distribution pattern in the Prydz Bay was ascribed to the influence of water masses with different 226Ra signals.Based on the relationship between 226Ra activity and salinity,three water masses were identified:(1) the antarctic summer surface water(AASSW) with a characteristics of high salinity and high content of 226Ra;(2) the ice-melted water(IMW) with a characteristics of low salinity and low content of 226Ra;and(3) the Prydz Bay deep water(PDW) with a characteristics of high salinity and intermediate content of 226Ra.226Ra in the Prydz Bay deep water was assumed to be maintained only by the supply from the seabed sediments.The fractions of the above three water masses were estimated by mass balance calculation of salinity and 226Ra activity.Results show that the AASSW fractions decrease from the deep open ocean to inshore,while the IMW and PDW fractions increase.The maximum fractions of the IMW and the PDW occur in the eastern and the western regions along the front of the Amery ice shelf,respectively,testifying the major flow into the shelf occurs at the eastern end and exits from the west. 国际极地年中国行动计划项目;国际海底区域研究开发“十一五”项目(DYXM-115-02-4-06);福建省自然科学基金杰出青年基金项目(2009J06026)